Brief acceptance and commitment therapy for children and adolescents with type 1 diabetes - Stefanescu, Cristina; Nechita, Aurel; Iacob, Claudia Iuliana (Frontiers in Psychology, 2024)
Introduction Children and adolescents with diabetes face challenges that can significantly impact their quality of life. Investigating psychological interventions for stress management can equip them with the skills needed to cope with type 1 diabetes. This study investigated the impact of a brief Acceptance and Commitment Therapy (ACT) intervention on stress management, diabetes acceptance, psychological flexibility, and patient-doctor relationships among this population. Methods A total of 55 children, and adolescents from Romania participated in a four-session ACT intervention for type 1 diabetes. The evaluation instruments used were the Perceived Stress Scale for Children (PSS-C), Acceptance and Action Diabetes Questionnaire (AADQ), Children’s Psychological Flexibility Questionnaire (CPFQ), and Patient-Doctor Relationship Questionnaire (PDRQ-9). Results The participants (mean age = 14.14, SD = 2.26; 67% girls) reported lower stress levels, increased acceptance of diabetes, and greater psychological flexibility after the intervention. Additionally, the patient-doctor relationship was enhanced, potentially improving patient adherence to treatment. Positive qualitative feedback mirrored previous ACT research in the paediatric population, highlighting the beneficial role of experiential activities and metaphors when working with this target group. Discussion This study adds to the growing body of evidence supporting the effectiveness of ACT in enhancing healthy coping strategies among children and adolescents with chronic illnesses.